Assessing General Knowledge and Nutritional Knowledge on the Role of Vitamin D, Attitudes, and Behavior Toward Sun Exposure Among Tertiary Students in Oman - Neela A. Sampat; Mohammed AlRizeiqi; Musthafa Mohamed Essa; Lyutha Al-Subhi; Samir Al-Adawi; M. Walid Qoronfleh (Advances in Public Health)
Conclusions: The constructed questionnaire showed satisfactory validity and reliability. The study identified a generally poor level of knowledge about vitamin D among students, highlighting the need for targeted educational strategies to improve awareness and promote better health outcomes.